Design Dashboard Monitoring Teacher Performance Assessment at Cinta Kasih Tzu Chi High School - Sugiyanti, Sri Dewi; Widayanti, Riya; Ulum, M Bahrul; Firmansyah, Gerry; Azizah, Anik Hanifa (Pandawan Sejahtera Indonesia, 2022)
Teachers are one of the main components in the world of education where they have a role in improving the quality of education. Where the quality of this education can be seen from the quality of teachers, but the quality of teachers is not only determined by the way of teaching and learning in the classroom, therefore it is necessary to conduct an assessment of teacher performance to measure the duties and responsibilities and obligations of each teacher. So to make it easier to analyze data and see the quality of teachers, a dashboard is designed to monitor teacher performance assessments that have been set by Cinta Kasih Tzu Chi High School based on document studies and interviews with school principals. Dashboard is one solution to present data in the form of visualization which is considered to provide clarity of information to be conveyed. This dashboard design uses a user centric method to describe the end-user design process that influences how a design is formed by utilizing Google Data Studio which will present information based on key performance indicators in graphic form to make it more interactive and easy to understand.